2009
DOI: 10.3945/jn.108.095091
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Deficiencies Are Associated with Impaired Immune Response and Higher Burden of Respiratory Infections in Elderly Ecuadorians

Abstract: The proportion of the Latin American population above age 65 y is expected to rise substantially. To better define the prevalence of infectious diseases and micronutrient deficiencies, assess immunological status, and evaluate associations between nutritional status and infection, we performed a cross-sectional study of elderly Ecuadorians in a low-income peri-urban community in Quito, Ecuador. Culturally adapted questionnaires, delayed type hypersensitivity (DTH) skin response, micronutrient, and immunologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 25 publications
0
45
0
7
Order By: Relevance
“…, 54 in their study of the effect of obesity on risk of influenza, pointed to the need to examine the effects of diet and exercise on risk of influenza infection. Previous research, mainly focusing on populations in developing nations, linked malnutrition and micronutrient deficiency with respiratory infection 55 , 56 , 57 , 58 . Several studies also demonstrated benefits of chronic moderate exercise in stimulating immune function and increasing serum concentrations of vitamin D (25 (OH) D) 59 , 60 , 61 .…”
Section: Discussionmentioning
confidence: 99%
“…, 54 in their study of the effect of obesity on risk of influenza, pointed to the need to examine the effects of diet and exercise on risk of influenza infection. Previous research, mainly focusing on populations in developing nations, linked malnutrition and micronutrient deficiency with respiratory infection 55 , 56 , 57 , 58 . Several studies also demonstrated benefits of chronic moderate exercise in stimulating immune function and increasing serum concentrations of vitamin D (25 (OH) D) 59 , 60 , 61 .…”
Section: Discussionmentioning
confidence: 99%
“…No se apreció una variación de la prevalencia de la defi ciencia de zinc o de cobre relacionada con la edad, contrariamente a lo observado en otros estudios que han descrito un aumento de la prevalencia de zinc en ancianos a medida que se incrementa la edad 11 o están hospitalizados 12 , lo que probablemente se explicaría porque que nuestros adultos mayores residían en sus hogares, eran autovalentes y no tenían restricciones relacionadas con la edad en el acceso a alimentos fuentes de zinc. Otros estudios realizados en adultos mayores de nuestra región han mostrado también altas prevalencias de defi ciencia de zinc 13,14 o zinc y cobre 15 .…”
Section: Prevalencia De Deficiencia De Zn Y Cu En Adultos Mayores -Munclassified
“…Estudios realizados en distintos países muestran que los adultos mayores constituyen un grupo que presenta una elevada prevalencia de defi ciencia de zinc, especialmente en los grupos más pobres, en aquellos que se encuentran institucionalizados u hospitalizados y en los países en vías de desarrollo [11][12][13][14][15][26][27][28] . Sin embargo, la información referente a la prevalencia de la defi ciencia de cobre es prácticamente inexistente.…”
Section: Prevalencia De Deficiencia De Zn Y Cu En Adultos Mayores -Munclassified
See 2 more Smart Citations